2013
DOI: 10.1177/0300060513484436
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-22 expression in hepatocellular carcinoma and its correlation with ezrin protein

Abstract: Objective: Expression of microRNA-22 (miR-22) and ezrin protein (a membrane-cytoskeleton linking protein) in hepatocellular carcinoma (HCC) was investigated. Methods: Specimens of HCC and paracancerous tissue (control; $5 cm away from tumour tissue) were collected from 192 patients. miR-22 expression was detected by real-time polymerase chain reaction; ezrin protein expression in tumour tissue was assessed immunohistochemically. Associations between miR-22 expression and clinicopathological features of HCC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…MiR-22 has been determined to be a regulator or an inhibitor in diverse cancers, including osteosarcoma, prostate cancer, cervical cancer, lung cancer, [44]breast cancer[45], colorectal cancer[46], gastric cancer [47, 48], ovarian cancer[49], acute myeloid leukemia[50], medulloblastomas[51], endometrial endometrioid carcinomas[52], esophageal squamous cell carcinoma[53] and hepatocellular carcinoma[54]. The study by Zhou et al [55] found that miR-22 is downregulated in HCC and that its expression is associated with the differentiation, metastasis and prognosis of carcinomas. They also found that the expression of miR-22 in hepatocellular carcinoma is significantly associated with histological differentiation and is negatively correlated with the expression of ezrin protein.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-22 has been determined to be a regulator or an inhibitor in diverse cancers, including osteosarcoma, prostate cancer, cervical cancer, lung cancer, [44]breast cancer[45], colorectal cancer[46], gastric cancer [47, 48], ovarian cancer[49], acute myeloid leukemia[50], medulloblastomas[51], endometrial endometrioid carcinomas[52], esophageal squamous cell carcinoma[53] and hepatocellular carcinoma[54]. The study by Zhou et al [55] found that miR-22 is downregulated in HCC and that its expression is associated with the differentiation, metastasis and prognosis of carcinomas. They also found that the expression of miR-22 in hepatocellular carcinoma is significantly associated with histological differentiation and is negatively correlated with the expression of ezrin protein.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, miRNAs are a powerful predictor of prognosis for cancer patients. Recently, several studies have shown the validity of miRNAs as prognostic markers in HCC (35,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). Upregulation of miR-9, miR-17-5p, miR-18, miR-25 and miR-590-5p/3p presented a high metastatic potential and a shorter survival in patients with HCC (35,(67)(68)(69)(70).…”
Section: Mirnas In Hcc Diagnosis and Prognosismentioning
confidence: 99%
“…In several cancers, miR-22 has been shown to be associated with differentiation, metastasis and prognosis. In HCC, miR-22 is especially down regulated [ 24 ]. Down-regulation of miR-30a in HCC is strongly associated with decreased disease-free survival.…”
Section: Resultsmentioning
confidence: 99%